Usual Tumour at an Unusual location – Solitary Sporadic Scapular Sessile Osteochondroma - Neeraja Myreddy; K.P. Varalakshmi; P. Sravani; B. Chaitanya (International Journal of Medical Research and Review, 2014)
Osteochondromas is one of the common bone tumour account for 35-46% of cases. These are most commonly seen on the metaphysis of a long bone, but they can arise from any bone which is preformed from cartilage and also involves flat bones like ilium and scapula. Scapular involvement is noted in 3 – 4.6 % of cases and patients usually are affected by winging of scapula. It is common in young patients, usually below 30 years of age, with a ratio of males to females of 2:1. We present a male patient diagnosed with solitary asymptomatic scapular osteochondroma with review of literature.